PENGARUH TERAPI BERMAIN BERCERITA TERHADAP TINGKAT KECEMASAN PADA ANAK USIA PRASEKOLA (3-5 TAHUN) AKIBAT HOSPITALISASI - Fetriani, Renty; Agung Riyadi, Dharizal, (JURNAL MEDIA KESEHATAN, 2017)
Anxiety is the impact of hospitalization experienced by pre-school children who can disrupt the child's development and healing process. This study aims to determine the influence of play therapy tells the story of anxiety levels of preschoolers who undergo hospitalization. Experimental pre experimental method using a pretest-postest one group design. Sampling technique is accidental sampling with sample of 30 respondents. Paired Test with significance level 95% (α <0,05). The results showed that the level of anxiety level before the play therapy tells story 28.00 and after the play therapy tells story 21.77, p value = 0.001 (<0.05) means there is a difference in children before and after doing play storytelling therapy is 6.33. The conclusion that the play storytelling therapy should be an alternative to decreasing the level of anxiety in children who underwent hospitalization In Dr. Rsud. M.Yunus Bengkulu. It is hoped that other researchers will be able to examine other factors that affect children's anxiety, such as anxiety due to separation, loss, injury, and pain. The research can be done by multiplying the sample being studied and using the comparison group, and the way of random sampling to obtain maximum results